2015
DOI: 10.1016/j.juro.2015.04.090
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Model of K-RAS and β-Catenin Induced Renal Tumors Expresses High Levels of E2F1 and Resembles Human Wilms Tumor

Abstract: Background Wilms tumor (WT) is the most common renal neoplasm of childhood. We previously showed that restricted activation of the WNT/β-catenin pathway in renal epithelium late in kidney development is sufficient to induce small primitive neoplasms with features of epithelial WT. Metastatic disease progression required simultaneous addition of an activating mutation of the oncogene K-RAS. Here, we sought to define the molecular pathways activated in this process and their relationship to human renal malignanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We previously reported that coordinate activation of KRAS and b-catenin in murine kidneys causes the formation of primitive renal epithelial neoplasms that are histologically consistent with epithelial predominant WT and that are characterized by excessive ERK and AKT activation (Clark et al, 2011;Yi et al, 2015). To investigate whether KRAS mutations are present in human WT, we profiled 19 human WT specimens using a multiplex PCR, multiplex primer extension, and capillary electrophoresis (SNaPShot method) screen (Dias-Santagata et al, 2010;Lovly et al, 2012;Su et al, 2011).…”
Section: Kras Mutations and Increased Akt Activation Are Present In Hmentioning
confidence: 99%
“…We previously reported that coordinate activation of KRAS and b-catenin in murine kidneys causes the formation of primitive renal epithelial neoplasms that are histologically consistent with epithelial predominant WT and that are characterized by excessive ERK and AKT activation (Clark et al, 2011;Yi et al, 2015). To investigate whether KRAS mutations are present in human WT, we profiled 19 human WT specimens using a multiplex PCR, multiplex primer extension, and capillary electrophoresis (SNaPShot method) screen (Dias-Santagata et al, 2010;Lovly et al, 2012;Su et al, 2011).…”
Section: Kras Mutations and Increased Akt Activation Are Present In Hmentioning
confidence: 99%
“…To explore the consistent gain at chromosome 12 observed in this KWT cohort and reported in other WT populations as well, we examined the OncoScan array data for somatic mutations in KRAS, which is the only of 9 genes included on this platform to be located on chromosome 12 and which has been shown in a transgenic WT model to drive disease progression (Clark et al, 2011;Yi et al, 2015). CNG at 12p12.1, the KRAS locus, was observed in 14 of the KWTs (47%), and 6 of these children (43%) are confirmed deceased.…”
Section: Kras Mutationsmentioning
confidence: 89%
“…2325 We have shown that coordinate activation of Ras with β-catenin leads to rapidly progressive, metastatic tumors that demonstrate markedly increased canonical β-catenin pathway activation. 23,24 In large series, similar activation has been demonstrated in the majority of human WT. 2628 Collectively, this suggests the canonical β-catenin pathway may represent a potential therapeutic target in WT, particularly in those patients with more advanced or high risk disease.…”
Section: Introductionmentioning
confidence: 60%
“…We have shown that a gene expression signature that distinguishes a mouse model and human WT from normal human kidney or other neoplasms includes marked up-regulation of c-Myc. 24 Mutations in the YEATS domain of the MLLT1 gene have recently also been linked to the development of WT and are characterized by increased MYC expression. 55 Prior work has shown that kidneys of mice harboring activating mutations of K-Ras and β-catenin restricted to the renal epithelium develop metastatic WT and have significantly increased c-Myc and Birc5 ’s protein product, survivin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation